Physiotherapy patients in intensive care unit - Miszewska, Agnieszka; Miszewski, Waldemar; Siminska, Joanna; Głowacka, Iwona; Ulenberg, Grzegorz; Cyrankiewicz, Waldemar; Nowacka, Krystyna; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Regulation of the Minister of Health dated 20/12/2012 on medical standards of conduct in the field of Anaesthesiology and intensive therapy, for carrying out the activities of healing in section § 2.2 intense therapy defines as: "any proceedings to maintain vital functions, and treatment of patients in life-threatening States, caused by potentially reversible renal failure one or more basic body systems, in particular the respiration, cardiovascular, central nervous system". However, in point § 12.1. We read that "Treatment of patients under intensive care in the hospital is an interdisciplinary". Annex 1 to this regulation refers to the work of physiotherapist in the ICU (INTENSIVE CARE UNITS) and reads as follows: "the equivalent of at least 0.5 FTE-physical therapist-up to a range of benefits to be performed (the third reference level)". [6]